Profil Kemampuan Literasi Matematika Ditinjau Dari Adversity Quotient Pada Pembelajaran Berdiferensiasi - Ratna Fertikawati; Gunawan Gunawan; Sri Solihah (Universitas Galuh, 2025)
In differentiated learning, improving mathematical literacy skills and understanding adversity quotient in students is very important to create an effective learning process, where students are not only recipients of information, but are able to think critically, adapt, and contribute their ideas. The implementation of this study aims to identify the mathematical literacy profile of grade VII H SMP Negeri 2 Mandiraja consisting of 36 students for the 2024/2025 school year reviewed from the adversity quotient level. The method used is qualitative descriptive by grouping students into three types, namely climbers, campers and quitters. In selecting subjects, it is carried out based on the value of the adversity quotient questionnaire or adversity response profile (ARP) and consideration from the teacher (purposive sampling). In collecting data, an adversity quotient questionnaire, written test questions regarding mathematical literacy skills, and interviews were carried out with the selected subjects. The analysis of the data uses data reduction from the results of written tests and interviews, the presentation of data from the analysis results and the conclusion of conclusions. The results were analyzed using source triangulation based on the process in mathematical literacy, namely formulating, employing, and interpretating mathematical concepts in various contexts. The results of the study showed that 1) Students with the climbers type have been able to carry out the process of formulating, employing, and interpretating in solving mathematical literacy problems; 2) Students with the camper type have been able to carry out the process of formulating, employing, and interpretating in the process of solving mathematical literacy problems; and 3) Students with the quitter type are only able to carry out the formulation process in solving mathematical literacy problems.